Design and evaluation of a subcutaneous contraceptive implant training simulator. Issue 1 (17th July 2019) - Dery, Samuel K.K.; Kaufmann, Elsie E.; Marzano, David; Deininger, Michael; Asem, Charity K.; Sienko, Kathleen H.
Abstract: Objective: To design and fabricate a subcutaneous contraceptive implant insertion simulator, and to characterize the performance of nursing students trained with and without the simulator. Method: A cross‐sectional study was conducted on nursing students in Ghana who had no previous training in the insertion of contraceptive implants. They were given standardized training in insertion of implants from 25 April to 26 April, 2016, and then were randomly assigned to an intervention or control group. The control group watched insertions of live implants while the intervention group practiced using the simulator. Local materials were used to fabricate the simulator. The performance of both groups was assessed after the training. Results: The participants consisted of 50 nursing students. Those in the intervention group were more likely to: insert the implant accurately (95.2% vs 78.4%, P <0.001); take less time to complete an insertion (mean of 33.6 seconds vs 42.2 seconds, P <0.001); and commit fewer errors (1.9 vs 2.5, P =0.005) compared to the control group. In addition, participants rated the simulator high on 11/11 of the product requirements with the teaching (93.2%), learning (91.4%), and skill acquisition (88.6%) requirements being the highest rated. Conclusion: A low‐cost, locally fabricated simulator is an effective tool for augmenting the current training protocol by improving insertion skills of contraceptive implants. Abstract : Novices trained with the implant insertion simulator were able to perform error‐free simulated insertions more accurately and quickly compared with the current mode of training.